Políticas linguísticas aplicadas pelo curso letras: libras da Universidade Federal de Goiás - UFG - Souza, Bianca Esteves da Silva (2024)
Is known that the diffusion of Brazilian Sign Language – Libras – has been occurring exponentially in recent years, more precisely through the legislation adopted by the country since 2002. The creation of legislation that recognizes Libras as a means of communication and social interaction for the deaf community allows access to spaces previously only occupied by speakers of other languages. In this sense, the deaf community becomes part of the university context, and there is a marked demand for Libras Letters courses, courses that promote the Libras in the national context, through public and private universities distributed throughout the five regions of the country. In this context, this research project called Linguistic policies applied to the course Letters: Libras at UFG, aims to answer the following research questions: How are the policies for the use of Libras configured in the course of Letters: Libras at the Federal University of Goiás? How are these policies implemented? To answer these questions, in this work qualitative research was carried out based on the instrument of data analysis based on documentary research. The use of this method enables a comprehensive perspective of the current panorama of the university that will be studied and allows a greater understanding of the study on the trajectory of the linguistic planning choices adopted by the Libras Languages course - UFG. The research brings together institutional documents of the university and the course, using as a theoretical reference authors who propose a theoretical approach on linguistic policies of the deaf community in general, as is the case of REAGAN (2010) and SPOLSKY (2004, 2009), as well as authors who highlight the linguistic policies adopted in Brazil, such as BRITO (1995), CALVET (2007), OLIVEIRA (2003), QUADROS (2014).